Detection of Molecular Motion in Lyophilized Myelin by Nuclear Magnetic Resonance - Lecar, Harold (1971)
Proton resonance spectroscopy was used to determine the state of the hydrocarbon regions in lyophilized and resuspended samples of nerve myelin. Measurements of the resonance line width indicate considerable freedom of motion within the hydrocarbon moiety of the myelin samples. Sharp thermal transitions of the line width were observed, suggesting that lyophilized myelin is in a liquid crystalline state.